Fossilized anuran soft tissues reveal a new taphonomic model for the Eocene Geiseltal Konservat-Lagerstätte, Germany - Falk, D; Wings, O; Unitt, R; Wade, J; McNamara, ME (Springer Nature, 2024)
The Eocene Geiseltal Konservat-Lagerstätte (Germany) is famous for reports of three dimensionally preserved soft tissues with sub-cellular detail. The proposed mode of preservation, direct replication in silica, is not known in other fossils and has not been verified using modern approaches. Here, we investigated the taphonomy of the Geiseltal anurans using diverse microbeam imaging and chemical analytical techniques. Our analyses confirm the preservation of soft tissues in all body regions but fail to yield evidence for silicified soft tissues. Instead, the anuran soft tissues are preserved as two layers that differ in microstructure and composition. Layer 1 comprises sulfur-rich carbonaceous microbodies interpreted as melanosomes. Layer 2 comprises the mid-dermal Eberth-Katschenko layer, preserved in calcium phosphate. In addition, patches of original aragonite crystals define the former position of the endolymphatic sac. The primary modes of soft tissue preservation are therefore sulfurization of melanosomes and phosphatization of more labile soft tissues, i.e., skin. This is consistent with the taphonomy of vertebrates in many other Konservat-Lagerstätten. These findings emphasize an emerging model for pervasive preservation of vertebrate soft tissues via melanosome films, particularly in stagnation-type deposits, with phosphatization of more labile tissues where tissue biochemistry is favorable.